2017
DOI: 10.29303/jpft.v2i2.288
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Scaffolding Konseptual dalam Pembelajaran Group Investigation Terhadap Prestasi Belajar Fisika Siswa SMA dengan Pengetahuan Awal Berbeda

Abstract: Abstract-The aim of this research is to find out the effect of conceptual scaffolding strategy in Group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
3
0
5
Order By: Relevance
“…The average increase in student learning outcomes after being given a scaffolding-assisted learning cycle 5E learning model using learning tools developed at 0.31 with moderate criteria. This is in line with Rahmatiah et al, (2016) who found that scaffolding can improve students achievement. Handoko & Winarno, (2019) in their research also found that addition of scaffolding in teachers learning media, can improve students achievement.…”
Section: Resultssupporting
confidence: 90%
“…The average increase in student learning outcomes after being given a scaffolding-assisted learning cycle 5E learning model using learning tools developed at 0.31 with moderate criteria. This is in line with Rahmatiah et al, (2016) who found that scaffolding can improve students achievement. Handoko & Winarno, (2019) in their research also found that addition of scaffolding in teachers learning media, can improve students achievement.…”
Section: Resultssupporting
confidence: 90%
“…Several other researchers have examined the application of scaffolding and the SSCS learning model, among others: the application of scaffolding with discussion methods(Alan Deta, 2017), the influence of constructivism-based Scaffolding (Indrawati, 2017), designing scaffolding to solve problems (Cheng et al, 2015), metacognitive scaffolding (Huertas, Lo, & Sanabria, 2016;Jumaat & Tasir, 2016), the application of Scaffolding to achieve independence (Nurhayati, 2017), the application of scaffolding in Investigation Group Learning (Rahmatiah, H, & Kusairi, 2016), SSCS integrated with metacognitive strategies (Yusnaeni, Corebima, Susilo, & Zubaidah, 2017), the effectiveness of SSCS and Cooperative Problem Solving (CPS) (Reahanah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pengetahuan awal merupakan bekal pengetahuan peserta didik untuk memperoleh pengetahuan baru [13]. Pengetahuan awal dapat digali sebelum proses pembelajaran.…”
Section: Pendahuluanunclassified